Educação olímpica nos Jogos Rio 2016: entre o conhecimento e o mundo da vida - Kirst, Flavio Valdir (2019)
In 2016, for the first time in history, the Olympic and Paralympic Games took place in one Latin American country. In addition to providing the physical and logistical structure for its accomplishment, it is the host city's responsibility to offer an educational program during the seven years preceding the opening ceremony of the Games (NAUL et al., 2017). Transforma, an education program of the Organizing Committee for the Rio 2016 Olympic and Paralympic Games, was developed between 2013 and 2016, reaching 16 thousand schools in more than 3 thousand municipalities of all Brazilian states. In order to fill the evaluations gap in this type of program (GRAVER et al., 2010; NIKOLAUS, 2013), something that has also worry the International Olympic Committee (INTERNATIONAL OLYMPIC COMMITTEE, 2014), our goal was to measure the reach of theTransforma program, considering the official data, the report of its managers and the perception of the multiplier teachers. It is an ex-post facto research, with a pre-experimental design, using as an analytical tools, questionnaire, interview, document analysis and geoprocessing techniques. In the program investigated, stand out the quality, dynamic format, fluid and objective of the material produced and the formations carried out, the diversification of means for the delivery of it educational content and the capacity of articulation with several public and private agencies for the reach of their goals. The results indicate that Transforma program activities are characterized more by the conceptual and procedural dimensions of the contents than by the attitudinal dimension (COLL et al., 1998). Likewise, they are characterized more by the didactic approaches in Olympic Education oriented to knowledge and to experience than to the approaches oriented towards competition and the world of life (NAUL, 2008). It was observed that the formal generality of the Transforma objectives, which are to create opportunities for elementary and middle school students to contact the Games, to try out new sports and to experience Olympic and Paralympic values, was evidenced in the knowledge acquired by multipliers teachers and their actions in schools, as well as in the experiences provided and the perceived impacts on the students reached. The main protagonists were physical education teachers. The main beneficiaries were students from schools with high levels of educational development, located in urban centers. Most of the actions focused on the southeastern region of the country. The main fragilities observed concern the lack of action of the governmental spheres, discontinuity of the educational legacy due to the temporality of the program and lack of a consistent evaluation of the results. It is believed that through Transforma, knowledge of Olympic values and their symbols, as well as the teaching of new sports, has probably reached a level never reached before in Brazil.